2021
DOI: 10.3389/fnins.2021.622729
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing Eyetronix Flicker Glass and Patching for Treatment of Amblyopia in Children Reveals Similar Improvements in Vision

Abstract: PurposeRecently, Eyetronix Flicker Glass (EFG) has been introduced as a novel treatment for amblyopia. It alternatively deprives the visual input of each eye rapidly (e.g., 7 Hz). However, whether it is comparable with standard patching therapy is unclear. In this randomized clinical trial, we evaluate the efficacy of an EFG therapy as treatment for amblyopia in children and compare it to the patching therapy.MethodsWe tested 31 children (aged 4–13 years) with amblyopia. They were assigned into one of the two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…43 The improvement in stereopsis is debatable. 24 , 25 , 44 , 45 The findings from this study should not be compared to these findings directly. First, the binocular balance was quantified while EFG was on in this study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…43 The improvement in stereopsis is debatable. 24 , 25 , 44 , 45 The findings from this study should not be compared to these findings directly. First, the binocular balance was quantified while EFG was on in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Additional amblyopic studies have also revealed that visual acuity and stereopsis can be improved at 7 Hz. 24 , 25 Therefore, we hypothesized that dichoptic alternative flicker stimuli could modify binocular interaction by the time difference between interocular excitatory and inhibitory responses, which in turn affects sensory eye balance in binocular processing.…”
mentioning
confidence: 99%
“…Both show that these visual improvements can be sustained for up to 1 year after the treatment [ 32 , 33 ]. A future study should directly investigate the effects of longitudinal inverse deprivation on various visual functions, such as interocular suppression and monocular contrast sensitivity of the deprived eye, stereopsis, and whether changes or improvements in these visual functions following inverse patching persist [ 13 , 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jost et al (10), recently showed amblyopic visual acuity gains and stereopsis gains with dichoptic movie therapy on a Nintendo 3DS screen comparable to patching. Flicker glasses-somewhat similar to Wang's study, can provide amblyopia therapy with success similar to patching (11).…”
mentioning
confidence: 80%